Awareness of standard precautions, circumstances of occurrence and management of occupational exposures to body fluids among healthcare workers in a regional level referral hospital (Bertoua, Cameroon) - Innocent Takougang; Fabrice Zobel Lekeumo Cheuyem; Billy Ralph Sanding Ze; Forlemu Fabiola Tsamoh; Hortense Mengong Moneboulou (BMC, 2024)
Abstract Background Healthcare workers (HCW) are exposed to infectious agents within biological materials including blood, tissues, other body fluids and on medical supplies, contaminated surfaces within the care delivery environment. Trends in occupational injuries are influenced by the level of awareness and observance of standard precautions (SP) among HCWs. This study aimed to assess the level of awareness of SP, exposure to body fluids, reporting pattern and management among HCWs in a Referral Hospital. Methods The present hospital-based cross-sectional study was carried out from 1st November 2020 to 31st May 2021. The exhaustive sampling method was used and a total of 120 consenting HCWs were invited to participate. A self-administered questionnaire addressed questions related to knowledge, experience, circumstances of exposure, reporting, management of occupational exposure to body fluids, hepatitis B vaccination status. Data were analyzed using R Statistic version 4.3.1. A p-value < 0.05 was considered significant. Results Out of the 120 participating HCWs, 104 (86.7%) reported at least one accidental exposure to body fluids over the last year. Men (aOR = 4.19; p = 0.277) and HCWs aged 35 and over (aOR = 4.11; p = 0.114) were more at risk for AEB even though the difference was not statistically significant. Nurses/midwives (aOR = 65.9; p-value = 0.0005) and cleaners (aOR = 14.7; p-value = 0.0438) faced the highest risk of exposure. Lack of knowledge (79%) and patient agitation (49%) were the most reported reasons for exposure. Half of the participants (53%) reported that they used a personal protective equipment during care. Face mask (59.2%) and gowns (30.8%) were the most commonly used PPE. Most HCWs (62%) did not report AEB. Half of the affected HCWs (50.8%) received a course of post-exposure antiretroviral therapy. Few HCWs (4.2%) were fully immunized against Hepatitis B. Conclusions Most HCWs reported an accidental exposure to body fluids over the last year. Midwives and nurses were disproportionally affected socio-professional groups. Two-thirds of the AEB were undeclared. Only half of the participants reported using PPE systematically. Hepatitis B vaccination coverage was low. There is need to strengthen the observance of standard precautions, including preventive vaccination and the systematic reporting and management of AEB.